FREQUENT USERS OF EMERGENCY MEDICAL SERVICES IN A METROPOLITAN CITY: INDIVIDUAL- AND SYSTEM-LEVEL CONSIDERATIONS. (20th December 2022) - Martinez, Beatrice; Aranda, Maria; Aguilar, Iris; Sanko, Stephen; Vega, William
Abstract: Frequent 911 calls from older adults place a significant burden on emergency response systems. Drawing from key informant interviews, we explore factors implicated in repeated Emergency Medical Services (EMS) among older people in the City of Los Angeles and provide system and policy recommendations to mitigate overuse of EMS 911 calls. Los Angeles Fire Department (LAFD) dispatch call records documented 370, 016 EMS encounters from 202, 471 unique individuals over 50 from 2012 to 2016. Frequent 911 callers over the age of 50 (n=8), family members (n=6), Los Angeles Fire Department (LAFD) personnel (n=10), and community service providers (n=3) participated in in-depth, qualitative interviews to understand individual- and system-level factors that increase the likelihood of repeated calls. All interviews were audio recorded, transcribed, and analyzed thematically. Guided by Grounded Theory, two themes emerged across all interviewee groups pointing to factors that contributed to 911 calls: 1) The Nature of 911 Calls; 2) Barriers to Access. Patients and family members were aligned on a third theme: 3) Previous Encounters: Interactions with emergency care providers, while LAFD and service providers were in agreement on a fourth theme: 4) The Role of EMS Responders and Community Providers. All groups provided recommendations for the theme, 5) Change the System so that 911 calls do not serve as the default choice. Findings demonstrate the need to improve coordination between LAFD, medical and human service providers. Care coordination can support individual- and system-level supports for patients and families to address their needs and reduce repeated EMS use.